PERAN ISTRI SEBAGAI TKW DALAM PEMENUHAN KEBUTUHAN KELUARGA TINJAUAN SOSILOGI HUKUM ISLAM : Studi Kasus di Kelurahan Tangkil Kecamatan Wlingi Kabupaten Blitar - Ahmad Habib Afandi; Muhammad Muhammad (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
There is a shift in roles and factors and impacts to meet family needs. Where in the past the wife in the household was only limited to housework and taking care of the children, but in recent times the wife has also acted as the main actor in meeting the family's needs. In this case, quite a few wives leave the country to work and become female workers. This research uses qualitative methods using a field approach or field research. Data collection was carried out by observation, interviews and documentation. The author uses data analysis techniques, namely descriptive data, to analyze data from research results in accordance with existing facts. Based on the research results which are in accordance with the role of the wife in fulfilling family needs using a sociological study of Islamic law in Tangkil Village, the role of the wife as a female worker is to fulfill needs. family and to be able to build their own house.